CGIAR at the global land forum 2025: Bridging science and land governance - Yomayuza, Karoll Valentina (2025)
With more than 1,300 delegates from 90 countries, the tenth Global Land Forum (GLF) turned Bogotá into the epicenter of international debate on land rights. In this setting, CGIAR contributed its perspective from applied research, participating in the decision-making spaces of the International Land Coalition (ILC) and presenting locally grounded solutions.